Surrogate test performance for SARS‐CoV‐2 neutralizing antibodies (nAbs) for convalescent plasma (CCP): How useful could they be?. Issue 12 (27th October 2021) - Wendel, Silvano; Fachini, Roberta; Fontão‐Wendel, Rita C. L.; Mello, Ralyria; Velasquez, Carlos Vinícius; Machado, Rafael Rahal Guaragna; Brito, Mayra Altobelli; Amaral, Marcelo; Soares, Camila Pereira; Achkar, Ruth; Scuracchio, Patrícia; Miyaji, Sandra Cristina; et al.
Abstract: Background: COVID‐19 high‐titer CCP selection is a concern, because neutralizing antibody (nAb) testing requires sophisticated labs and methods. Surrogate tests are an alternative for measuring nAb levels in plasma bags, including those that are pathogen‐reduced. Study design/methods: We studied a panel consisting of 191 samples from convalescent donors tested by nAb (CPE‐VNT), obtained from 180 CCP donations (collection: March 20–January 21) and 11 negative controls, with a total of 80 and 111 serum and plasma samples (71 amotosalen/UV treated), with nAb titers ranging from negative to 10, 240. Samples were blindly tested for several surrogates: one anti‐RBD, two anti‐spike, and four anti‐nucleocapsid tests, either isolated or combined to improve their positive predictive values as predictors of the presence of high‐titer nAbs, defined as those with titers ≥160. Results: Except for combined and anti‐IgA/M tests, all isolated surrogate tests showed excellent performance for nAb detection: sensitivity (98.3%–100%), specificity (85.7%–100%), PPV (98.9%–100%), NPV (81.3%–100%), and AUC (0.93–0.96), with a variable decrease in sensitivity and considerably lower specificity when using FDA authorization and concomitant nAb titers ≥160. All surrogates had AUCs that were statistically different from CPE‐VNT if nAb≥160, including when using combined, orthogonal approaches. Conclusions: Surrogate tests (isolated or in combination) have an indirect good performance in detecting the presence of nAb, with lower sensitivity and specificity when high nAb titer samples are used, possibly accepting a considerable number of donors whose nAb titers are actually low, which should be evaluated by each laboratory responsible for CCP collection.